Основные морфологические особенности головного мозга и черепномозговых нервов дельфинов и других китообразных. Сообщение I - Агарков, Г.Б.; Хоменко, Б.Г.; Слезин, В.Б. (Вестник зоологии, 1973)
The enormous brain of Cetacea in the process of evolution developed in tight connection with the most complex adaptive activity under new ecological conditions. On the basis of the authors' own data and those from literature, the peculiarities of the brain macro- and microscopic structure in some Cetaced represontatives are mentioned. The relation is explained between development or reduction of definite brain areas and various functional rearrangements of an organism in transition from ground to water habitat. Morphology of some pairs of cranial nerves is described. On the basis of the authors' own data,' the points are determined where some cranial nerves exit out of the brain stem, their topography and morphology in intra- and extracranial areas are presented. The peculiarities in morphology of oculomotor, trochlear, trigeminal, abducent and facial nerves are determined in all the species of dolphins under study as compared with ground mammals and man.